Elevated CO2 Improves Photosynthesis Under High Temperature by Attenuating the Functional Limitations to Energy Fluxes, Electron Transport and Redox Homeostasis in Tomato Leaves - Pan, Caizhe; Ahammed, Golam Jalal; Li, Xin; Shi, Kai (Frontiers in Plant Science, 2018)
Elevated atmospheric CO2 improves leaf photosynthesis and plant tolerance to heat stress, however, the underlying mechanisms remain unclear. In this study, we exposed tomato plants to elevated CO2 (800 µmol mol-1) and/or high temperature ( 42 °C for 24 h), and examined a range of photosynthetic and chlorophyll fluorescence parameters as well as cellular redox state to better understand the response of photosystem II (PSII) and PSI to elevated CO2 and heat stress. The results showed that, while the heat stress drastically decreased the net photosynthetic rate (Pn), maximum carboxylation rate (Vcmax), maximum ribulose-1,5-bis-phosphate (RuBP) regeneration rate (Jmax) and maximal photochemical efficiency of PSII (Fv/Fm), the elevated CO2 improved those parameters under heat stress and at a 24 h recovery. Furthermore, the heat stress decreased the absorption flux, trapped energy flux, electron transport, energy dissipation per PSII cross section, while the elevated CO2 had the opposing effects that eventually decreased photoinhibition, damage to photosystems and reactive oxygen species accumulation. Similarly, the elevated CO2 helped the plants to maintain a reduced redox state as evidenced by the increased ratios of ASA:DHA and GSH:GSSG under heat stress and at recovery. Furthermore, the concentration of NADP+ and ratio of NADP+ to NADPH were induced by elevated CO2 at recovery. This study unraveled the crucial mechanisms of elevated CO2-mediated changes in energy fluxes, electron transport and redox homeostasis under heat stress, and shed new light on the responses of tomato plants to combined heat and elevated CO2.